Molecular identification of Aspergillus isolates from Magellanic penguins - Melo, Aryse Martins (2021)
Aspergillosis is an important disease in marine birds and has a mortality rate of 50% in Magellanic penguins (Spheniscus magellanicus) in captivity. Molecular biology allows the precise identification of Aspergillus to species level, which is important since cryptic species may show differences in their virulence attributes and in their antifungal susceptibility. This work aimed to perform molecular identification and the itraconazole susceptibility profile of Aspergillus clinical isolates collected from Magellanic penguins with proven aspergillosis.